Anti-diabetic Effect of Sprouted Trigonella foenumgraecum L. Seed Solid Dosage Form in Low-dose Streptozotocin Induced Diabetic Rats - Mishra, Ashwini Kumar; Sahoo, Pravat Kumar; Lal, Ganesh; Bajpai, Meenakshi; Dewangan, Hitesh Kumar (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Trigonella foenum-graecum L (Fenugreek) is an annual herb, mainly cultivated for its seed as well as for its sprouts. Pharmacological investigations reported anti-bacterial, anti-diabetic, anti-cancer, anti-diarrheal, anti-hypercholesteremic, and antiinflammatory activities of Trigonella foenum-graecum L. Aim: The purpose of this study was to accentuate on formulation of granules and investigate the effect of germinated Trigonella foenum-graecum L. (TFG) granules in Diabetes mellitus (DM) rats induced by streptozotocin as fenugreek retains hypoglycemic property. Materials and Methods: Granules of germinated TFG powder were arranged by means of several excipients comprising diverse amounts of super disintegrants by (wet) granulation method and proceed for the solid dosage form evaluation. Further, in-vivo study was performed in STZ induced DM Wister rats for four weeks. TFG granules 1600mg/kg and Glibenclamide 0.45 mg/kg (as a positive control for comparison) were orally administrated and evaluate the diabetics in rats. Results: All evaluation parameter are correct: as in standard tablet. The STZ (Streptozotocin) induced rats the treatment with the Drug (Glibenclamide) and TFG granules significantly lowered the blood plasma glucose levels by 36% (mean ± SD glucose 120 ± 0.6 mg/dL (p < 0.001)) and 38% (mean ± SD glucose 114 ± 0.4 mg/dL; p < 0.001) respectively after 4 weeks of treatment when compared to T2DM (Type 2 Diabetes mellitus) rats. Conclusion: Experimental studies had shown that bioactive compounds found in Trigonella Foenum graceum herb have potential to cure diabetes especially due to the presence of unique chemical constituent including trigonelline, galactomannan and amino acid 4-hydroxy isoleucine. These findings suggested that TFG granules may be an alternative medicine for the management of DM.
Keywords: Trigonella foenum-graecum; Fenugreek; Anti-diabetic; Tablet; Diabetes; mellitus